PENGEMBANGAN MEDIA INTERAKTIF BERMUATAN KELOMA PADA TOPIK KEUNIKAN KEBIASAAN MASYARAKAT DI SEKITARKU UNTUK MENINGKATKAN LITERASI BUDAYA SISWA KELAS IV SEKOLAH DASAR - Siti Aldian Nurjanah; Yuyu Yuliati; Mahpudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the low understanding of students towards culturalliteracy is shown by the tendency of students more interested dengan budaya inforeign culture than budaya local culture typical of Majalengka, as belum well as theabsence of media to mengkaitkan literasi link cultural literacy. The problem tersebutrequires a solution in the form of learning media that integrate elements kearifan oflocal wisdom with technology, so that the solution offered in this study iniis thedevelopment of Interactive media charged Keloma uuntuk improve cultural literacy.Metode penelitian yang digunakan dalam penelitian ini Research and Development(R&D) dengan model 4D (Define, Design, Develop, dan Disseminate). Stages ofresearch include analisisNeeds Analysis, perancanganmedia design, developmentproduk yang divalidasi of expert-validated products,sertaas well astrials todeployment. The results of this study inishowed that Keloma media was declaredfeasible and practical to use with validation ahli of material experts from lecturerssebesarat 82.5% and from teachers at 86.25%, ahlimedia experts at 100%, ahlilinguists at 92.8%, and ahli cultural experts at 95%. The results responof theteacher's response sebesarwas 86%, and respon the student's responsesebesarwas 91.1%. While the effectiveness test through paired sample t-testshowed a significant difference between the pretest and posstest results. So it isproven that Keloma media is effective in improving cultural literacy. PenelitianFurther research is expected dapatto developsimilar media with cakupan budayayang wider cultural coverage luas and integrate fitur interaktif other interactivefeatures to pengalaman siswa optimize the student experience.